Corrosion resistance of AISI 316L coated with an air-cured hydrogen silsesquioxane based spin-on-glass enamel in chloride environment. (October 2017) - Lampert, Felix; Christiansen, Alexander Bruun; Din, Rameez Ud; Gonzalez-Garcia, Yaiza; Møller, Per
Highlights: The efficiency of HSQ-based barrier coatings on 316L substrate is investigated. Excessive thermal oxidation of the substrate leads to coating failure. The chemical coating stability increases with increasing coating polymerization. Curing in air is inadequate for HSQ-based corrosion barrier coatings. Abstract: The efficiency of thin hydrogen silsesquioxane (HSQ) −based corrosion barrier coatings on 316L substrates after oxidative thermal curing at 400–550 °C in air was investigated. Infrared spectroscopy and electrochemical impedance spectroscopy showed that an increasing curing temperature leads to progressing coating densification, accompanied by decreasing barrier properties. Cyclic polarization measurements indicated that defects due to substrate oxidation are detrimental for the substrate passivity. Insufficiently polymerized coatings showed poor chemical stability in neutral salt spray testing and the chemical coating stability increased with curing temperature. Oxidative curing was found inadequate as polymerization treatment of HSQ-based corrosion barrier coatings on 316L substrate.